"Heat and destroy": bronchoscopic-guided therapy of peripheral lung lesions - Eberhardt, Ralf; Kahn, Nicolas; Herth, Felix (Respiration, 2010)
Although the treatment of choice for stage I lung cancer patients is surgery, a lot of patients have a high comorbidity and are medically inoperable. Bronchoscopy, as a central technique in diagnosing lung cancer, has the potency to apply endoscopic therapy to small lung lesions in a minimally invasive way in patients with high risk for surgery. Unfortunately, bronchoscopy cannot always reach lesions in the peripheral lung, in particular the smaller lesions. Therefore, new guidance techniques like virtual bronchoscopy and electromagnetic navigation are now available and instead of using the systems as a diagnostic tool, these techniques may provide an option for therapeutic interventions to inoperable lung tumor patients. With endoscopic fiducial marker placement for robotic radiosurgery and endoluminal high-dose brachytherapy, local radiotherapy of peripheral lung tumors becomes feasible, reducing radiotherapy-induced toxicity. Radiofrequency tissue ablation through the working channel of a flexible bronchoscope may be a chance of making a diagnosis and a curative treatment in one endoscopic session. However, technical improvements of the ablation probes are currently necessary to expand the sizes of ablated areas. Even though the technologies are very attractive and pilot data are extremely encouraging, more studies establishing selection criteria and best utility are needed.
Gesehen am 27.02.2023